Penyiraman Tanaman Mawar Secara Otomatis Berdasarkan Kelembaban Menggunakan Metode Fuzzy Tsukamoto - Fajri, Nurul; Islamiyah, Mufidatul (JURNAL SISTEM KOMPUTER ASIA, 2025)
Watering plants manually usually causes various problems. One of them is the lack of standards for watering the same water in each watering process which will cause the rose plants being cared for to experience excess or lack of air, so that the rose plants will experience root freezing and various diseases. Watering plants economically and on time is one solution. So it would be helpful if there was an automatic watering system that could water evenly using a soil moisture sensor as a parameter to determine watering time. Effective watering of rose plants requires a method so that the control system can achieve what is desired. One control system that is relatively good at producing output responses is the fuzzy method. This fuzzy method is widely used because it is easy to understand and apply in helping the decision making process. The results of soil moisture testing produce a linear graph which shows that if the humidity value is below 55 then the watering duration output is long, if the humidity value is between 55-70 then the watering duration is medium, and if the humidity value is above 70 then the watering duration output is fast or short